Interactive Motion-Sensing Game for Improving Physical Education in Students with Intellectual Disabilities - Rakhmadi, Aris; Puspitasari, Yuliana; Yasin, Fatah; Sulistyo Nugroho, Yusuf; Fadlillah, Umi (Mestro: Jurnal Teknik Mesin dan Elektro, 2025)
Students with intellectual disabilities often face challenges in physical education due to limited motor coordination, reduced engagement, and difficulties following traditional instructional methods. To address this, motion-sensing technology, particularly Kinect-based educational games, presents a promising solution by offering interactive and gamified learning experiences. This study explores the development and implementation of a Kinect-based educational game designed to enhance motor skills and engagement in students with intellectual disabilities. The game focuses on throwing exercises, providing real-time feedback through visual and auditory cues to reinforce learning. The study was conducted at SLB-C YPSLB Surakarta, involving 20 students with intellectual disabilities and five special education teachers. A pre-test and post-test evaluation was used to assess students' motor skill improvement and engagement levels before and after using the game. The results demonstrated a 26.3% increase in throwing accuracy, a 26.9% rise in engagement levels, and a significant reduction in reaction time, indicating the game's effectiveness in enhancing physical coordination and participation. Teacher feedback highlighted the game's usability, ability to maintain student focus, and alignment with PE learning objectives. Although the findings showed positive learning outcomes, several challenges, such as the initial adaptation period and the need for a wider variety of games, were identified. Future research should focus on customizing difficulty levels, varying physical activities, and AI-powered adaptive learning to meet the needs of individual students. This study highlights the potential of motion-sensing educational games as an effective tool for inclusive and engaging physical education for students with intellectual disabilities.